2005
DOI: 10.1123/ijsnem.15.3.252
|View full text |Cite
|
Sign up to set email alerts
|

Fluid, Electrolyte, and Renal Indices of Hydration during 11 Days of Controlled Caffeine Consumption

Abstract: This investigation determined if 3 levels of controlled caffeine consumption affected fluid-electrolyte balance and renal function differently. Healthy males (mean +/- standard deviation; age, 21.6 +/- 3.3 y) consumed 3 mg caffeine . kg(-1) . d(-1). on days 1 to 6 (equilibration phase). On days 7 to 11 (treatment phase), subjects consumed either 0 mg (C0; placebo; n= 20), 3 mg (C3; n = 20), or 6 mg (C6; n = 19) caffeine . kg(-1) . d(-1) in capsules, with no other dietary caffeine intake. The following variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 31 publications
3
54
1
5
Order By: Relevance
“…11,53 Although caffeine is a mild diuretic, consumption of Յ500 mg/day does not cause dehydration or chronic water imbalance. 54,55 Caffeine is a ventilatory stimulant with anti-inflammatory and bronchoprotective effects. 56 Caffeine has been linked to dyspnea on exertion from central and peripheral chemoreceptor stimulation.…”
Section: Figurementioning
confidence: 99%
“…11,53 Although caffeine is a mild diuretic, consumption of Յ500 mg/day does not cause dehydration or chronic water imbalance. 54,55 Caffeine is a ventilatory stimulant with anti-inflammatory and bronchoprotective effects. 56 Caffeine has been linked to dyspnea on exertion from central and peripheral chemoreceptor stimulation.…”
Section: Figurementioning
confidence: 99%
“…The available literature has shown that doses of more than about 250-300 mg caffeine (equivalent to 2-3 cups of coffee) have a mild diuretic effect, while doses of less than 250 mg do not show any effect. 57,58 Thus, doses of caffeine equivalent to the amount normally found in standard servings of tea, coffee and carbonated soft drinks appear to have no diuretic action. 57 In contrast, alcohol has a more potent diuretic effect and 1 gram is sufficient to increase urine output by 10 ml.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Opposing this viewpoint, Armstrong [6] concluded that the diuretic effect of caffeine is overstated and further may be minimised for habitual caffeine consumers. In support of this view, Armstrong et al [7] provided strong evidence for no caffeine-induced diuresis (<500 mg/24 hours) in males undergoing daily activities with no strenuous physical training.…”
mentioning
confidence: 60%